PERTENTANGAN IMPLEMENTASI ATURAN KONSTITUSI DAN SYARI’AH DARI PUTUSAN UJI MATERI MAHKAMAH KONSTITUSI PADA UU PERKAWINAN NOMOR 1 TAHUN 1974 PASAL 43 AYAT 1 - Fauziyah, Begum (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2012)
The discretion of constitutional court to issue material test on marital lawNumber I/1974 verse 43 on unmarried –born child to get law protectioncauses a debate among societies particularly among muslim societies. Withthis consideration, this constitution emphasizes that there is a civil lawrelationship between the child and his or her biologic father if it can beproven. As a result of the new regulation on this issue, an unmarried-bornchild gets his or her legal hereditary, inheritance right and guardian right.The dispute on the issue has not found clear solution to answer all the debateamong societies. This writing tries to explore the form of mediation whichaims at making clear the implementation of unmarried-born child status regulation of which it can make constitutional regulation and Islamic law in line considering muslim society as the majority in Indonesia.